Hermann Blohm. Gründer der Werft Blohm & Voss - Schröder, Hans Joachim (Mäzene für Wissenschaft, 2011)
As founders of the Blohm & Voss-Werft, Hermann Blohm and his partner Ernst Voss have gained importance far beyond Hamburg. By giving the company international recognition, he made a major contribution to the city's enormous upswing as a port and industrial location after 1877. In Hanseatic restraint, the patriarchal shipyard manager who managed his company with determination and rigour as a family-owned company, stepped back completely behind his work. After considerable initial difficulties, the shipyard expanded into a large enterprise. The ups and downs of the shipyard's history reflect the development of Germany in the Weimar Republic between the Wilhelminian era, the quest for power, the First World War, revolution and a new beginning. At the same time and primarily, this history comes alive in the biography of Hermann Blohm, who was also one of the donors of the Hamburgische Wissenschaftliche Stiftung (Hamburg Scientific Society).